2014
DOI: 10.5539/ijbm.v9n2p17
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Business Ethics Held by Accountancy and Finance Students in the University of Botswana

Abstract: The current study is borne out of an interest on the ethical views of accounting majors, as well as evaluating their perceptions on certain ethical behaviour. The study is timely since it was undertaken at a time when the University of Botswana's Accountancy degree curriculum had been reviewed and a course in ethics in accounting was introduced. The Attitudes Towards Business Ethics Questionnaire (ATBEQ) was distributed to students who had completed the ethics and auditing courses. Willing respondents were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Most importantly, Phatshwane et al . () contended that ethical education and behavior can be learned.…”
Section: Discussion Of Major Thematic Findingsmentioning
confidence: 99%
“…Most importantly, Phatshwane et al . () contended that ethical education and behavior can be learned.…”
Section: Discussion Of Major Thematic Findingsmentioning
confidence: 99%
“…This particular study puts normativity (i.e., ethics) at the centre of the entrepreneurial process, equipping students with experiences of including ethics in business practices. As Phatshwane, Mapharing, and Basuhi () indicate, ethical behaviour can be learned, and starts developing in the early stages of life. The same holds for sustainable entrepreneurial competencies and entrepreneurial intentions; they are learnable constructs that have a strong foundation in the educational context and require higher order learning processes (Cope, ; Corbett, ).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the results of research by Tom & Biobele (2015) concluded that business morals are very important for companies to improve their business performance. Also, the results of research by Phatshwane et al (2014) concluded that business morals can expand the business so that they can guarantee business continuity. Furthermore, the research of Santosuosso (2013) found business morals can be one of the important aspects in the budget system which ultimately can improve business performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, the results of the research Tom & Biobele (2015) study concluded that ethics is very important for organizations to improve their ethical codes. Also, the results of the study of Phatshwane et al (2014) concluded that business ethics can expand the business. Furthermore, Santosuosso's research (2013) found that business ethics can be one dimension in the budget system which can ultimately improve business performance.…”
Section: Factors Causing the Food Industry Not Able To Maintain Contimentioning
confidence: 99%
See 1 more Smart Citation